حساب مردود مرجل البخار في محطات الطاقة الحرارية عند حمولات متغيرة وتحديد معامل الهواء الزائد الأمثل - علي, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن البحث دراسة تأثير بعض العوامل المؤثرة على الضياعات الحرارية الناتجة عن الاحتراق غير الكامل للوقود، على مردود مرجل البخار في محطات توليد الطاقة الكهربائية التقليدية، ويشمل البحث أيضاً تقييم الطرق المستخدمة لحل مشاكل الضياعات الحرارية، وتحديد العلاقة التي تربط بين حمولات المرجل، ومعامل الهواء الزائد على الضياعات الحرارية، والتحكم المباشر بتدفق الهواء للحصول على اقتصادية جيدة في عملية احتراق الوقود، وتحديد القيمة المثلى لمعامل الهواء الزائد في شروط عمل المرجل، والتي يجب تأمينها عن طريق أجهزة التحكم والأتمتة لمعدات المرجل من أجل تحقيق التوفير في استهلاك الوقود والحصول على القيمة المثلى لمردود المرجل. This research includes a study of the effect of some influencing factors on heat losses produced by the unburning fuel on the efficiency of Steam Boiler in the traditional Electric Power Plants. It contains a discussion of the used methods of losses problems, a determination of the relation between the boiler heat loads and the excess air coefficient on heat losses, the direct control of air flow in order to obtain a good economical burning of fuel process, and to determine the optimal value of excess air coefficient in condition of Boiler operation ,through using automatic controlled systems of boiler devices to economize fuel rate and the optimal value of Boiler Efficiency.